The Legacy of Roman Law in the German Romantic Era - James Q. Whitman (Princeton University Press, 2014)
THE GREAT ESCAPE is a movie about men escaping from a prisoner-ofwar camp in World War II. The Great Escape of this book is the story of mankindâ€™s escaping from deprivation and early death, of how people have managed to make their lives better, and led the way for others to follow. One of those lives was my fatherâ€™s. Leslie Harold Deaton was born in 1918 in a tough coal-mining village called Thurcroft in the South Yorkshire coalfi eld. His grandparents Alice and Thomas had given up agricultural labor in the hope of doing better in the new mine. Their eldest son, my grandfather Harold, fought in World War I, returned to the â€œpit,â€ and eventually became a supervisor. For my father, it was diffi cult to become educated in Thurcroft between the wars because only a few children were allowed to go to high school. Leslie took odd jobs at the pit; like the other boys, his ambition was that, one day, he would get the chance to work at the face. He never made it; he was drafted into the army in 1939 and sent to France as part of the ill-fated British Expeditionary Force. After that debacle, he was sent to Scotland to be trained to be a commando; there he met my mother and was â€œfortunateâ€ enough to be invalided out of the army with tuberculosis and sent to a sanitarium. Fortunate because the commando raid on Norway was a failure, and he would almost certainly have died. He was demobilized in 1942 and married my mother, Lily Wood, the daughter of a carpenter in the town of Galashiels in the south of Scotland.